2007
DOI: 10.1177/000313480707300809
|View full text |Cite
|
Sign up to set email alerts
|

Scout Anteroposterior and Lateral CT Scans as a Screening Test for Thoracolumbar Spine Injury in Blunt Trauma

Abstract: Anteroposterior and lateral radiographs have traditionally been required to clear the thoracolumbar spine (TLS) after blunt trauma. The routine use of CT scans led to a pilot trial to determine if CT scout images can accurately evaluate the TLS after blunt trauma. The purpose of the study was to determine the sensitivity, specificity, positive and negative predictive values of CT scout images for the evaluation of the TLS. Patients admitted to our level II trauma center requiring CT evaluation of the chest, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…For studies with a criterion standard likely to correctly classify the presence of TL-spine fractures, the TL-spine fracture prevalence was 8-41%. [24][25][26][27][28][29][30][31][32][33][34][35] Based on these studies, the estimated pretest probability (prevalence) for TL-spine fracture in blunt trauma was 15%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For studies with a criterion standard likely to correctly classify the presence of TL-spine fractures, the TL-spine fracture prevalence was 8-41%. [24][25][26][27][28][29][30][31][32][33][34][35] Based on these studies, the estimated pretest probability (prevalence) for TL-spine fracture in blunt trauma was 15%.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies examined the diagnostic accuracy of history or physical examination, including complaints of or findings of spine pain or tenderness upon palpation, lateral spine pain upon palpation, distracting injury, abnormal neurologic examination, altered consciousness, intoxication, palpable spine deformity, back bruising, skin abrasion/ laceration, physician gestalt, and the whole physical examination. 25,27,31,32,34,41,[43][44][45][46][47][48][49][50][51][52] The most useful physical examination to rule-in a TL-spine fracture was a palpable spine deformity with +LR=15.3 (95% CI=7.1-33.0, I 2 =0%, p=0.79). 46,47 No single negative physical examination finding (such as lack of spine tenderness) significantly reduced the probability of a TL-spine fracture (see Appendix D2).…”
Section: History and Physical Examinationmentioning
confidence: 99%
“…Conventional radiography is generally accepted the primary diagnostic process for chest trauma patients today 39-40 but other studies reported that CT is more effective as a beginning scanning method for management of emergency chest trauma cases [41][42][43][44][45]. In polytrauma patients, it is difficult to get direct radiographs and the results are nondiagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of CT scouts has been reported to add value to detection of musculoskeletal findings by CTonly [2][3][4]. Several studies suggest the use of CTscouts to rule out vertebral fractures, with sensitivity ranging from 70 to 98.7% and specificity 99.7-100% [5][6][7]. However, little is known about the possibilities of detection of chest or pelvic injury by CT scouts.…”
Section: Introductionmentioning
confidence: 99%